Short-Versus Long-Term Credit and Economic Performance : Evidence from the WAEMU - Gbenyo, Kodzo (IMF Working Papers; Working Paper ;, 2010)
This paper studies the link between financial development and economic growth in the West African Economic and Monetary Union (WAEMU). Using panel data for WAEMU countries over the period 1995-2006, the results suggest that while financial development does support growth in the region, long-term bank financing has a greater impact on economic growth than short-term financing because long-term projects have higher returns adjusted for risks. Given that in the WAEMU short-term credit accounts for about 70 percent of credit to the private sector, WAEMU countries are less able to reap the full benefits of improvements in their financial systems. The results also highlight the importance of macroeconomic stability, a creditor-friendly environment, political stability, and the availability of long-term financial resources in fostering banks' supply of long-term loans.